Simultaneous operations in patients with combined pathology of the thyroid and parathyroid glands - Ya. V. Tielushko; K. O. Loburets (Zaporozhye State Medical University, 2024)
The combination of thyroid and parathyroid gland pathology is a rather rare combination of diseases that occurs in 2.0-5.0 % of patients with thyroid pathology, and their combination in the population is less than 0.1 %. The aim of the study. To improve the diagnosis and treatment of patients with combined pathology of the thyroid and parathyroid glands. Materials and methods. The retrospective analysis covers the period from January 2013 to December 2023, during which 912 patients with thyroid pathology were examined and operated on. Examination of patients was carried out according to the method of diagnosis of combined surgical pathology developed by us (utility model patent No. 128139, Ukraine). The gender structure was dominated by female patients: 773 (84.8 %) and 139 (15.2 %). The average age of patients in the study group was 54.9 ± 11.7 years. Results. After the examination, combined surgical pathology was found in 201 (22.1 %) patients. In 36 (17.9 %) of them, the pathology of the prostate gland was detected as a concomitant disease. In the structure of parathyroid pathology in 35 (97.2 %) patients, a benign lesion of the prostate gland was detected, in 1 (2.8 %) - cancer of the parathyroid gland. In the structure of the main thyroid pathology, 14 (38.9 %) patients were diagnosed with multinodular euthyroid goiter, 4 (11.1 %) with mononodous euthyroid goiter, 9 (25.0 %) with diffuse toxic goiter, 3 (8, 3 %) - mononodous toxic goiter, 6 (16.7 %) - papillary thyroid cancer. Clinical symptoms of hypoparathyroidism were observed in 21 (58.3 %) patients after surgery. In 3 (8.3 %) patients, seroma of the neck wound was detected in the postoperative period. There were no fatalities. Conclusions. The use of the developed method of diagnosing combined surgical pathology makes it possible to detect concomitant surgical pathology in 22.1 % of patients with endocrine diseases, which requires simultaneous operative intervention. In the structure of combined surgical pathology, in 17.9 % of cases, a combination of diseases of the thyroid gland and parathyroid gland was observed. Simultaneous surgical intervention for combined thyroid pathology and diseases of the thyroid gland does not lead to an increase in perioperative complications and mortality.